Wheat germ cell-free system-based production of hemagglutinin-neuraminidase glycoprotein of human parainfluenza virus type 3 for generation and characterization of monoclonal antibody - Matsunaga, Satoko; Kawakami, Shiho; Matsuo, Izumi; Okayama, Akiko; Tsukagoshi, Hiroyuki; Kudoh, Ayumi; Matsushima, Yuki; Shimizu, Hideaki; Okabe, Nobuhiko; Hirano, Hisashi; Yamamoto, Naoki; Kimura, Hirokazu; et al. (Frontiers in Microbiology, 2014)
Human parainfluenza virus 3 (HPIV3) commonly causes respiratory disorders in infants and young children. Monoclonal antibodies (MAbs) have been produced to several components of HPIV3 and commercially available. However, the utility of these antibodies for several immunological and proteomic assays for understanding the nature of HPIV3 infection remain to be characterized. Herein, we report the development and characterization of MAbs against hemagglutinin-neuraminidase (HN) of HPIV3. A recombinant full-length HPIV3-HN was successfully synthesized using the wheat-germ cell-free protein production system. After immunization and cell fusion, 36 mouse hybridomas producing MAbs to HPIV3-HN were established. The MAbs obtained were fully characterized using ELISA, immunoblotting, and immunofluorescent analyses. Of the MAbs tested, single clone was found to be applicable in both flow cytometry and immunoprecipitation procedures. By utilizing the antibody, we identified HPIV3-HN binding host proteins via immunoprecipitation-based mass spectrometry analysis. The newly-developed MAbs could thus be a valuable tool for the study of HPIV3 infection as well as the several diagnostic tests of this virus.